2011
DOI: 10.1074/jbc.m111.287474
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis Type I, Unique Structure of Accumulated Heparan Sulfate and Increased N-Sulfotransferase Activity in Mice Lacking α-l-iduronidase

Abstract: Background: In Hurler syndrome, heparan sulfate (HS) accumulates and is associated with early childhood mortality. Results: Accumulated HS is abnormally highly sulfated and positively regulates N-deacetylase/N-sulfotransferase activity during HS biosynthesis. Conclusion:We have identified a positive feedback loop in HS biosynthesis in Hurler syndrome that exacerbates the disease. Significance: This will aid the design of therapeutic strategies for Hurler syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 45 publications
4
70
1
Order By: Relevance
“…The GAGs then were extracted separately from the BrM and NSR using a previously described method. 43 …”
Section: Hs Extractionmentioning
confidence: 97%
See 1 more Smart Citation
“…The GAGs then were extracted separately from the BrM and NSR using a previously described method. 43 …”
Section: Hs Extractionmentioning
confidence: 97%
“…The AMAC-labeled disaccharides were separated by RP-HPLC in duplicate/triplicate using a Zorbax Eclipse XDB-C18 RP-HPLC column (3.5 lm, 2.1 3 150 mm; Agilent Technologies, Stockport, UK), as described previously. 43,44 Disaccharide types were identified/quantitated in comparison with AMAC-labeled commercial disaccharide standards (Iduron). The experiments were performed in four batches (each containing young and old donors), which were run on separate days.…”
Section: Preparation and Analysis Of 2-aminoacridone (Amac)-labeled Dmentioning
confidence: 99%
“…Mucopolysaccharidosis (MPS) are a family of related lysosomal storage disorders which results from a mutation in one of the genes encoding enzymes from the catabolic pathway of the GAGs (Constantopoulos and Dekaban, 1978;Holley et al, 2011;McGlynn et al, 2004;Muenzer et al, 2009;Wilkinson et al, 2012;Wraith, 1995). This results in the impaired degradation of specific GAGs and accumulation of their derivatives in cells and tissues, leading to a wide variety of clinical manifestations (Coulson-Thomas et al, 2013;Giugliani et al, 2010;Muenzer, 2004;Muenzer et al, 2009;Ohmi et al, 2003;Wilkinson et al, 2012).…”
Section: Glycosaminoglycans and Proteoglycans In Neurodegenerative Comentioning
confidence: 99%
“…1 illustrate that the total GAG content is similar in all of the samples; however, the figure does not illustrate that differences may also exist in the distribution of the molecular weights of the GAG chains, the specific linear saccharide sequences within the chains, and/or the chemical modifications to the saccharides within the chains. This is well illustrated in murine MPS I brain and liver, where Holley et al demonstrated that affected mice showed accumulation of heparan sulfate that was highly sulfated at the N, 2-O and 6-O sites in brain and liver [20]. These issues become very important when one considers the possibility that certain specific GAG fragments may be the primary mediators of disease symptoms and complications in the MPSs [9].…”
Section: Primary Markersmentioning
confidence: 96%